(untitled) (Journal of Health, Population and Nutrition, 2009)
Shigella flexneri has been the most frequent cause of shigellosis in children in Iran. To evaluate the changes in frequency of serogroups, 302 Shigella species were isolated in 2003 from hospitalized children, aged less than 12 years, with acute diarrhoea in Tehran, Iran. The number of collected S. sonnei, S. flexneri, S. boydii, and S. dysenteriae isolates was 178 (58.9%), 110 (37.4%), 10 (3.3%), and 4 (1.3%) respectively. Most (94%) S. sonnei isolates were resistant to co-trimoxazole. They were, however, relatively or completely sensitive to 15 commonly-used antibiotics. The extracted plasmids showed 12 different profiles with two closely-related patterns constituting 70% of the total isolates. Ribotyping, using PvuII, HindIII or SalI restriction enzymes, generated a single pattern for all S. sonnei isolates. Data suggest that S. sonnei has become the predominant serogroup in children in the hospitals of Tehran. Key words: Antibiotic resistance; Antibiotics; Drug resistance, Microbial; Dysentery, Bacillary; Ribotyping; Shigella sonnei; Iran doi:10.3329/jhpn.v26i4.1884 J Health Popul Nutr 2008 Dec:26(4):426-430